Recurrent Acute Respiratory Infections in Children: Effectiveness and Safety of Phytotherapy - V. P. Vavilova; T. A. Vavilova; A. K. Cherkayeva (Union of pediatricians of Russia, 2015)
Recurrent respiratory infections in children lead to physical development disorders, formation of chronic nidi of infection, failure of adaptive mechanisms and degradation o immunobiological resisting barriers; this causes development of new diseases. Results of the presented non interventional clinical study confirm high safety profile and effectiveness of a therapeutic phytopreparation for recurrent respiratory infections.